Nursing diagnosis noncompliance of patients being treated by the high blood pressure program - Bertoletti, Altair Roriz; Costa, Alice Gabrielle de Sousa; Costa, Francisca Bertilia Chaves; Oliveira, Ana Railka de Souza; Oliveira, Célida Juliana de; Araújo, Thelma Leite de (Rev Rene, 2012)
Exploratory research conducted from November/2010 to February/2011with a sample of 38 patients with hypertension. The objective was to identify the nursing diagnosis of noncompliance in patients with hypertension treated by Primary Health of the County of Caucaia/Ceará. Data was collected based on defining characteristics and related factors to the diagnosis and submitted for evaluation by two nurses for diagnostic inference. Most participants were women, elderly, retired, with low education and family income, presence of comorbidities and polypharmacy. 36.8% of evaluated patients were diagnosed. The most frequent characteristics were indicative behavior of failure in adhesion and inadequate management of non-medication treatment and the most outstanding factor was the insufficient knowledge to the sequence of drug treatment regimen and non-medication treatment. We conclude that the diagnosis has been quite prevailing in this population, which may contribute to better guide the actions of nurses in primary care